2018
DOI: 10.1111/raq.12320
|View full text |Cite
|
Sign up to set email alerts
|

Applications of microalga Chlorella vulgaris in aquaculture

Abstract: Microalgae biomass is used in aquaculture as feed, growth enhancers and immunostimulants. Chlorella vulgaris is an important species with a good biomolecular composition. Commercially, it is one of the most commonly used microalga in aquaculture. Several studies confirmed its ability to improve nutrition, immunity, aquatic bioremediation, amelioration of stress, disease resistance of fish and inhibits bacterial quorum sensing when used appropriately. Despite claims of its benefits, C. vulgaris is reported to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(83 citation statements)
references
References 153 publications
(328 reference statements)
2
75
0
6
Order By: Relevance
“…Past research also reported that C. vulgaris is a potential source of renewable energy due to its high lipid content. However, the total lipid content is dependent on culture conditions [22]. In addition, studies using FTIR indicated that polyol and amide constituents in C. vulgaris played critical role in synthesizing palladium nanoparticles by reducing the metal ions in an eco-friendly and non-toxic process [23].…”
Section: Introductionmentioning
confidence: 99%
“…Past research also reported that C. vulgaris is a potential source of renewable energy due to its high lipid content. However, the total lipid content is dependent on culture conditions [22]. In addition, studies using FTIR indicated that polyol and amide constituents in C. vulgaris played critical role in synthesizing palladium nanoparticles by reducing the metal ions in an eco-friendly and non-toxic process [23].…”
Section: Introductionmentioning
confidence: 99%
“…The green microalga Chlorella is among the most common algal species used in aquaculture (Ahmad et al, 2020). Axenic Chlorella sp.…”
Section: Resultsmentioning
confidence: 99%
“…From the view of nutrition, C. vulgaris is rich in nutrients, containing 61.6% proteins, 12.5% fat, 13.7% carbohydrates, trace elements, various vitamins, and minerals, and is generally used as growth promoter and immunopotentiator ( Ahmad et al, 2018 ). Khani et al (2017) have studied the effect of C. vulgaris on immunological parameters of koi carp Cyprinus carpio .…”
Section: Microalgae Can Be Excellent Immunostimulants or Antioxidantsmentioning
confidence: 99%